Importance of obstetric nursing in reducing unnecessary interventions during labor (Research, Society and Development, 2023)
Objective: To identify the importance of obstetric nurses in reducing unnecessary interventions during natural childbirth. Methodology: An integrative review of the literature was carried out in the databases: Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online and Medical Literature Analysis and Retrieval System Online, with the descriptors: obstetric nursing, care models to health, childbirth, with inclusion criteria for a comprehensive search of the topic, where the final sample was 11 studies, which were used to form the discussion. Results: Through the general apparatus of the results, it is possible to see that the importance of obstetric nurses in reducing the use of interventions lies in the support they give to women in labor, improving this moment to the point where interventions are not needed, and it is completely natural. Conclusion: It was possible to verify that the obstetric nurse has a fundamental role in natural birth, both in promoting health and in reducing unnecessary interventions during this moment that needs to be healthy and natural. An important fact to be mentioned in this data collection is that this work was essential in the profile of the obstetric nurse in the face of humanized techniques during the birth process, as it is evident to describe this model of health strategy. Finally, we hope that the article has brought knowledge on this topic, considering a contribution role in future research in an efficient manner.